Effect of combining music media therapy with lower extremity exercise on elderly patients with diabetes mellitus - Li Ji; Jiao-Jiao Bai; Jiao Sun; Yue Ming; Li-Rong Chen (Elsevier, 2015)
Objective: To evaluate the compliance with lower extremity exercise and blood circulation in the feet of elderly diabetics following a combination of music media therapy and a lower extremity exercise regimen. Method: The 72 elderly diabetic patient subjects were divided into two groups: control group (n = 38) and intervention group (n = 34). Both groups were exposed to the same comprehensive therapy to control glucose levels. While the control group was given the lower extremity exercise, the intervention group received the extremity exercise in addition to the music media. Result: After three months of intervention, the adherence to the lower extremity exercise regimen in the intervention group was significantly higher than that of the control group (p < 0.05). Additionally, following six months of treatment, both the dorsal artery peak values and ankle-brachial indices (ABIs) showed significant differences between the control and intervention groups (p < 0.05). Conclusion: Music media treatment combined with lower extremity exercise can both significantly increase the extent of exercise compliance of elderly patients suffering from diabetes mellitus, as well as improve blood circulation in their feet.